The Association Between Telemedicine and Emergency Department (ED) Disposition: A Stepped Wedge Design of an ED‐Based Telemedicine Program in Critical Access Hospitals. Issue 3 (23rd April 2019) - Natafgi, Nabil; Mohr, Nicholas M.; Wittrock, Amy; Bell, Amanda; Ward, Marcia M.
Abstract: Purpose: To study the relationship between the availability and activation of emergency department‐based telemedicine (teleED) and patient disposition in Critical Access Hospitals (CAHs). Methods: A non randomized stepped wedge design examined 133, 396 ED visits in 15 CAHs that subscribe to a single teleED provider. Data were available for at least 12 months prior to teleED implementation and at least 12 months of post‐implementation. Primary analyses were conducted using multinomial logistic regression models with teleED availability (indicator of post‐teleED implementation period) and activation (indicator of utilization of teleED service) predicting discharge disposition adjusting for age, sex, and clinical diagnosis. Results: Patients for whom teleED was activated were more likely to be transferred [adjusted odds ratio (aOR) = 12.04; 95% confidence interval (CI), 10.97‐13.21] and more likely to be admitted to the local hospital (aOR = 3.23; 95% CI, 2.84‐3.67) than to be routinely discharged. This pattern was confirmed for patients presenting with chest pain, mental illness, and injury/poisoning. However, in the period following teleED implementation, patients presenting to EDs after telemedicine was available, but not necessarily utilized, were less likely to be admitted to the local hospital (aOR = 0.79; 95% CI, 0.76‐0.82) than to be routinely discharged. Conclusions: Telemedicine availability in CAH EDs is associated with a higher likelihood of routine discharges from the ED possibly due to changes in care associated with teleED implementation. The relationship between teleED use and disposition may be related to selection in activating teleED for cases more likely to require hospital inpatient care.